Reconstruction of Polyhalite Ore-Formed Temperature from Late Middle Pleistocene Brine Temperature Research in Kunteyi Playa, Western China - Jun Li; Wenxia Li; Weiliang Miao; Qiliang Tang; Yongshou Li; Xiaolong Yuan; Qingyu Hai; Yongsheng Du; Xiying Zhang (Geofluids)
Kunteyi Salt Lake (KSL), located in the northwest of the Qaidam Basin (QB), is rich in polyhalite resources. However, there is no relevant research on the ore-formed temperature of polyhalite in nature, such as KSL. The homogenization temperature (Th) of salt mineral inclusions can directly reveal the form temperature of minerals. In view of the poor diagenesis of polyhalite in KSL, almost no polyhalite crystals are formed. Therefore, the ore-formed temperature of polyhalite in KSL is revealed by using the Th of fluid inclusions in halite associated with polyhalite as a substitute index. A total of 472 Th data from 34 halite samples and 34 maximum homogenization temperature (ThMAX) data ranged from 17.1°C to 35.5°C, among which 24 data were concentrated at 17-23°C and the average value is 22.1°C. Brine temperature of other salt lakes in QB and paleoclimate characteristics of the study area were combined. It suggests that the temperature conditions of polyhalite mineralization in the study area are generally low. However, under the overall low-temperature background, polyhalite seems to be easily enriched at relatively high temperature; for example, the content of polyhalite is generally high in the first relatively dry and hot salt-forming period, and the brine temperature at the peak stage of polyhalite at 45 m is relatively high, which indicates that the high temperature conditions promote the formation of polyhalite in KSL. As far as the overall relationship between temperature and polyhalite is concerned, polyhalite is deposited at both low temperature and relatively high temperature, which verifies the previous understanding that polyhalite is a mineral with wide temperature phase, and also shows that temperature has a limited effect on polyhalite formation under natural conditions. In addition, combined with the chemical composition of halite fluid inclusions, it is found that the concentration of Mg2+ in nature has an influence on the temperature measurement process. According to the previous experimental research, speculate that the actual temperature of ancient brine and ore-formed temperature of polyhalite in KSL are lower than the measured Th. The confirmation of the influence of Mg2+ on temperature measurement is convenient for more accurate reconstruction of the metallogenic temperature of evaporite such as polyhalite. The research on the ore-formed temperature of KSL polyhalite enriches and perfects the polyhalite mineralization theory and provides theoretical basis for the basic and applied research of polyhalite.